AKUNTABILITAS DAN TRANSPARANSI PEMERINTAH DESA DALAM PENGELOLAAN ALOKASI DANA DESA DI DESA BONGKARAS KECAMATAN SILIMA PUNGGA-PUNGGA, KABUPATEN DAIRI”. - Parhusip, Poltak Teodorus; Girsang, Christy (UNIKA Santo Thomas, 2023)
The purpose of this study is to analyze the Accountability and Transparency of village fund allocation management in Bongkaras Village. The formulation of the problem in this study is